Boosting ESL Vocabulary: The Role of Interactive Method in Language Acquisition - Yuli Ari Sandy; Barli Bram (Hasanuddin University, 2024)
This study investigated the effectiveness of interactive methods in enhancing vocabulary acquisition among English as a Second Language (ESL) students. Focusing on innovative teaching strategies, the research examined how interactive activities such as games, role-playing, and technology-assisted learning affect vocabulary retention and use. The research question is